Epilogue: Where Do We Go from Here? - Peters-Davis, Norah; Shultz, Jeffrey (Challenges of Multicultural Education, 2005)
This chapter summarizes many of the pedagogical strategies that faculty have embraced to create a climate that encourages self-reflection. It explore the commonalities that emerge from the writings of the faculty and students who contributed to this book so that others can use their insights to reflect on what is happening in their own classrooms and on their campuses. Reed's and Brian Girard's reflections on their learning processes challenge typical notions of White men as ignorant and resistant to learning about their own racism, ethnocentrism, and unearned privilege. Once faculty members begin to focus on their own role in the dialogue, the opportunity for continued growth presents itself with every class. The ultimate challenge of multicultural education: to create a space where all persons, whether they are from the majority or the minority, understand their own identity, their relationships to others who are different from them, and the real implications of diversity for society.